2021
DOI: 10.1111/pce.14014
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma atroviride‐emitted volatiles improve growth of Arabidopsis seedlings through modulation of sucrose transport and metabolism

Abstract: Plants host a diverse microbiome and differentially react to the fungal species living as endophytes or around their roots through emission of volatiles. Here, using divided Petri plates for Arabidopsis-T. atroviride co-cultivation, we show that fungal volatiles increase endogenous sugar levels in shoots, roots and root exudates, which improve Arabidopsis root growth and branching and strengthen the symbiosis. Tissue-specific expression of three sucrose phosphate synthase-encoding genes (AtSPS1F, AtSPS2F and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 89 publications
(165 reference statements)
0
21
0
Order By: Relevance
“…Especially, increasing evidences showed that endophyte can directly and indirectly promote the growth and secondary metabolites of its host plants through various ways [ 12 14 ]. For example, endophyte can induced the development of its host plants by directly producing plant growth hormone themselves [ 12 ], or indirectly by promoting its host plants capacity of nutrients absorption and stress resistance [ 13 ]. Furthermore, endophyte can also produce bioactive compounds which are the same or similar to the secondary metabolites in its hosts [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, increasing evidences showed that endophyte can directly and indirectly promote the growth and secondary metabolites of its host plants through various ways [ 12 14 ]. For example, endophyte can induced the development of its host plants by directly producing plant growth hormone themselves [ 12 ], or indirectly by promoting its host plants capacity of nutrients absorption and stress resistance [ 13 ]. Furthermore, endophyte can also produce bioactive compounds which are the same or similar to the secondary metabolites in its hosts [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The many secondary metabolites produced by Trichoderma species are responsible for their highly antagonistic effects, contributing to the success of their application [ 12 ]. Additionally, the application of Trichoderma species successfully regulates root architecture, increasing the length of lateral and primary roots, leading to the more efficient uptake of nutrients by the plant, resulting in biostimulation [ 13 15 ]. The mechanism through which Trichoderma exerts biostimulatory effects involves multilevel communication with root and shoot systems, including releasing many active metabolites into the rhizosphere, thereby increasing plant growth and yield [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that VOCs may play a role in the biostimulatory and biocontrol activities of Trichoderma spp. [ 13 , 17 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The many secondary metabolites produced by Trichoderma species are responsible for their highly antagonistic effects, contributing to the success of their application [11]. Additionally, the application of Trichoderma species successfully regulates root architecture, increasing the length of lateral and primary roots, leading to the more efficient uptake of nutrients by the plant, resulting in biostimulation [12][13][14]. The mechanism through which Trichoderma exerts biostimulatory effects involves multilevel communication with root and shoot systems, including releasing many active metabolites into the rhizosphere, thereby increasing plant growth and yield [2].…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that VOCs may play a role in the biostimulatory and biocontrol activities of Trichoderma spp. [12,16,25].…”
Section: Introductionmentioning
confidence: 99%